SMART CADETS Prototype Design: Data-based RFID for Cadet Academic Hours Optimization Using ESP32 Microcontroller Media - Bambang Wijaya Putra; Parjan Parjan; M Efaldes Syahputra; Hana Fatiha; M Alamsyah; Afra Nabilah A (International Journal of Educational Review, 2023)
This paper focuses on Palembang Aviation Polytechnic cadets as students are directed to be able to form better personalities through mental, character, and physical development. Palembang Aviation Polytechnic forms the character of cadets who are disciplined, firm, and punctual. Cadets are required to take part in 8 hours of active learning by the Palembang Aviation Polytechnic's Cadet Code of Conduct (PT3). For time efficiency and ease of monitoring cadets' compliance with compulsory education, a data-based RFID tool was designed using an Arduino as an open and close system controller when a cadet taps an RFID card. Cadets are required to tap the RFID card that each individual has to ensure that cadets arrive and leave on time during learning hours. The system will not transmit data if cadets arrive before the specified time. After that, the data will be distributed to a spreadsheet as material for assessing each cadet.